FORMATION STAGES AND SOURCES OF THE PERALKALINE GRANITOID MAGMATISM OF THE NORTHERN MONGOLIA-TRANSBAIKALIA RIFT BELT DURING THE PERMIAN AND TRIASSIC - Yarmolyuk V.V.; Kovalenko V.I.; Zhuravlev D.Z.; Litvinovsky B.A.; Zanvilevich A.N.; Posokhov V.F.; Jahn B.-M.; Vorontsov A.A.; Sandimirova G.P.; Kuz'min D.V. (My University, 2001)
Rb-Sr and Sm-Nd isotopic systems were investigated in the peralkaline granitoids and comagmatic volcanic rocks, which compose the Northern Mongolia-Transbaikalia Belt (NMTB). The belt extends over more than 2000 km at a width of 200-300 km. It includes more than 350 syenite-granite plutons and a number of volcanic fields. The majority of plutons and volcanic sequences of the NMTB were formed in the end of the Paleozoic and beginning of the Mesozoic (main stage). The isotopic investigations were carried out in two key regions, which comprise typical and comprehensively studied associations of granitoids and volcanic rocks. The Rb-Sr isotopic dating showed that the main stage of NMTB formation began at 275 Ma and terminated at ca. 210 Ma. This stage is subdivided into several discrete magmatic episodes occurring in the Middle-Late Permian (275-250 Ma) and the Late Triassic (225-210 Ma). During each episodes, large (up to 2000 km2) volcano-plutonic structures were formed. The magmatism was located mainly in the western segment of the NMTB (northern Mongolia) in the Middle-Late Permian and in the eastern segment (Transbaikalia), in the Late Triassic. The movement of magma generation zones from the western to the eastern part of the belt with a displacement amplitude of ca. 800 km was related to the clockwise rotation of the North Asia continent above the mantle plume that controlled intraplate activity in the southern margin of North Asia in the Late Paleozoic and Mesozoic. The Sm-Nd and Rb-Sr isotopic data indicate that mantle-derived material played an essential role in the formation of peralkaline silicic magmas. The unusually high homogenization temperatures of melt inclusions in quartz phenocrysts from comendite (up to 1100°C) at H2O and F contents no lower than 1 wt % in the magmas suggest either significant (subcrustal) depths of silicic magma formation or their anomalous heating in crustal magma chambers owing to basaltic melt injection.
Keywords: Permian; Triassic; Northern Mongolia-Transbaikalia Belt; Мезозой::Триасовая; Mesozoic::Triassic; Paleozoic::Permian; Палеозой::Пермская